Tissue, cellular, and molecular level determinants for eye lens stiffness and elasticity - Cheng, Catherine (Frontiers in Ophthalmology, 2024)
The eye lens is a transparent, ellipsoid tissue in the anterior chamber that is required for the fine focusing of light onto the retina to transmit a clear image. The focusing function of the lens is tied to tissue transparency, refractive index, and biomechanical properties. The stiffness and elasticity or resilience of the human lens allows for shape changes during accommodation to focus light from objects near and far. It has long been hypothesized that changes in lens biomechanical properties with age lead to the loss of accommodative ability and the need for reading glasses with age. However, the cellular and molecular mechanisms that influence lens biomechanical properties and/or change with age remain unclear. Studies of lens stiffness and resilience in mouse models with genetic defects or at advanced age inform us of the cytoskeletal, structural, and morphometric parameters that are important for biomechanical stability. In this review, we will explore whether: 1) tissue level changes, including the capsule, lens volume, and nucleus volume, 2) cellular level alterations, including cell packing, suture organization, and complex membrane interdigitations, and 3) molecular scale modifications, including the F-actin and intermediate filament networks, protein modifications, lipids in the cell membrane, and hydrostatic pressure, influence overall lens biomechanical properties.